REKAM JEJAK TOKOH PEREMPUAN ACEH PENGEMBAN MISI PERDAMAIAN DALAM MEDIA MASSA ONLINE - Rismawati Rismawati; Lily Eky Nursia N (Master Bahasa, 2022)
This research is related to women who carry peace missions, women's rights fighters, and development inspirations in Aceh, who have received national and international awards, whose track records are markedly marked in online mass media. Aceh is known as an area that has a long history of women. Conflicts, earthquakes, tsunamis, and related to other political issues of course there are women who are behind these events. In this paper, the author will record women who have fought, or fought for peace and women's rights as well as the histories of women who have struggled to fill Aceh's development. This paper is limited to the 20th century Aceh region after the Aceh tsunami to the present, the 2000-2020 range. This range was chosen because this year is the range of conflict centers, earthquake and tsunami natural disasters, and peace agreements. This research was conducted using heuristic research methods and with a simple interpretation. The sources used are in the form of digital traces and online media. Based on the results of the research conducted, a long list of names of female peace fighters and women's rights fighters was found. However, in this paper, the biographical description will be limited to the names of four female figures who have received national and international awards, especially in fighting for peace and women's rights.